The Effect of Harvard Step Test on Vital Lung Capacity Among Medical Students at Tadulako University - Rahma Badaruddin; Ria Sulistiana; Fitriah Handayani; Yuli Fitriana; Mohammad Zainul Ramadhan; Muhammad Ihsan Akib; Junjun Fitriani; Muhammad Nasir; Geovani Ginting (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Background: According to the World Health Organization (WHO), a lack of physical activity contributed to 830,000 deaths annually in 2022. University students are among the populations with low levels of physical activity. Vital capacity is the maximum amount of air that can be expelled from the lungs, influenced by various factors including age, gender, exercise habits, smoking activity, nutritional status, and medical history. This study aims to determine the effect of physical exercise using the Harvard Step Test on vital lung capacity in students at the Faculty of Medicine, Tadulako University. Specifically, this study aims to determine the value of vital lung capacity before and after physical exercise and analyze the effect of physical exercise on changes in vital lung capacity in students at the Faculty of Medicine, Tadulako University.. Methods: This study employed a pre-experimental method with a One Group Pre-Test Post- Test design without a control group, involving 23 participants, both male and female. Sampling was conducted using a non-probability method with purposive sampling technique. The physical exercise intervention consisted of the Harvard step test for four weeks, with a frequency of three times per week for approximately five minutes per session. The results were analyzed using the Paired Sample T-test in SPSS software. Results: The average pre-test vital capacity was 2.64 liters, while the average post-test vital capacity was 3.24 liters, indicating an increase in vital capacity following the intervention. The comparative analysis using the Paired Sample T-test yielded a p- value<0.000 (p<0.05), indicating a significant effect of the Harvard step test on vital capacity. Conclusion: There is an effect of physical exercise using the Harvard step test method on the vital capacity of the lungs in students of the Faculty of Medicine, Tadulako University.